Educação permanente em saúde no processo de trabalho na atenção primária: uma teoria fundamentada nos dados - Araújo, Ana Beatriz Gouveia de (2023)
Continuing Health Education presents itself as a powerful tool to promote transformations desired by managers and workers to improve services and the health system. This study's main objectives are to understand Permanent Health Education in the work process of Primary Health Care from the perspective of professionals who work in the current context of the Unified Health System and to develop a theoretical model on Permanent Health Education in the work process in Primary Health Care in the current context of the Unified Health System. The study participants were formed by health professionals from the Basic Health Units that are part of the Western Health District of the city of Natal, Rio Grande do Norte, Brazil. This is a research with a qualitative approach that has as its methodological reference the Grounded Theory, with a structuralist approach proposed by Strauss and Corbin. Grounded Theory was chosen because it is a methodological approach that is rigorous during data collection and analysis, considering that the research will study a professional training strategy inserted into the routine and work process of professionals in a procedural manner. Data collection took place between January and May 2023 through in-depth interviews, based on the following guiding question: Talk about continuing education in your work process in primary health care. Data collection followed theoretical sampling, being carried out from three sample groups, the first composed of 16 nurses, the second by five managers and the third by a nursing technician and four community health agents. Data analysis was carried out simultaneously with data collection, with constant raising of new questions and carrying out comparative analysis, following open, axial and selective coding. The Atlas ti software, version 8, was used as a technological tool, with the appropriate license acquired. With the coding of the interviews, 1391 citations, 824 codes, four memos, 27 groups of codes and 16 networks or analytical diagrams were obtained from the analysis. After data analysis, the theoretical model was validated by the following groups: two researchers selected for their expertise in investigations, discussions and practices in Continuing Health Education; three researchers with expertise in the GT method; five participants from the study sample groups. The results achieved were divided into categories according to paradigmatic circumstances, conditions, action/interaction and consequences. The following representative categories of the phenomenon studied were elucidated: Pointing out needs and paths for implementing EPS in PHC; Facing the adversities of working in health and the need for applied knowledge and adequate working conditions; Proposing strategies and relationships that enhance the materialization of EPS; Establishing the advances arising from EPS in the context of PHC; and Declaring the difficulties of not implementing EPS in the health work process. The results provided the construction of the theoretical model that represents the understanding of Continuing Health Education in the Primary Health Care Work Process from the perspective of professionals working in the current context of the Unified Health System.